Bitburg in moral and political perspective - Hartman, Geoffrey H., 1929-2016 1929-2016 (Indiana Univ. Pr, 1986)
Examines the moral and political controversy surrounding President Reagan's intention to visit a cemetery in Bitburg, Germany, in 1985 during a visit commemorating the fortieth anniversary of the end of World War II and the opening of the concentration camps. The discovery that the cemetery also contained a small group of graves of SS officers prompted protests by Jews and American veterans.